Computed tomography-guided needle aspiration and biopsy of pulmonary lesions: a single-center experience in 1000 patients. (July 2013) - Poulou, Loukia S; Tsagouli, Paraskevi; Ziakas, Panayiotis D; Politi, Dimitra; Trigidou, Rodoula; Thanos, Loukas
Background: Computed tomography (CT)-guided fine needle aspiration (FNA) and biopsies are well-established, minimally invasive diagnostic tools for pulmonary lesions. Purpose: To analyze retrospectively the results of 1000 consecutive lung CT-guided FNA and/or core needle biopsies (CNB), the main outcome measures being diagnostic yield, and complication rates. Material and Methods: Patients considered eligible were those referred to our department for lung lesions. The choice of FNA, CNB, or both was based upon the radiologist's judgment. Diagnostic yield was defined as the probability of having a definite result by cytology/histology. Results: The study included 733 male patients and 267 female patients, with a mean (SD) age of 66.4 (11.4) years. The mean (SD) lesion size was 3.7 (2.4) cm in maximal diameter. Six hundred and forty-one (64%) patients underwent an FNA procedure, 245 (25%) a CNB, and 114 (11%) had been subjected to both. The diagnostic yield was 960/994 (96.6%); this decreased significantly with the use of CNB only (odds ratio [OR] 0.32; 95% CI 0.12–0.88; P = 0.03), while it increased with lesion size (OR 1.35; 95% CI 1.03–1.79; P = 0.03 per cm increase). In 506 patients (52.7%), a malignant process was diagnosed by cytopathology/histology. The complication rate reached 97/1000 (9.7%); complications included: hemorrhage, 62 (6.2%); pneumothorax, 28 (2.8%); hemorrhage and pneumothorax, 5 (0.5%); and hemoptysis, 2 (0.2%). It was not significantly affected by the type of procedure or localization of the lesion. The overall risk for complications was three times higher for lesions <4 cm (OR 3.26; 95% CI 1.96–5.42; P < 0.001). Conclusion: CT-guided lung biopsy has a high diagnostic yield using FNA, CNB, or both. The CNB procedure alone will not suffice. Complication rates were acceptable and correlated inversely with lesion size, not localization or type of procedure.